Synthesis of CLA-rich lysophosphatidylcholine by immobilized MAS1-H108A-catalyzed esterification: effects of the parameters and monitoring of the reaction process - Li, Daoming (Wiley, 2018)
Conjugated linoleic acid (CLA)‐rich lysophosphatidylcholine (LPC) with many proven beneficial effects is successfully synthesized by an immobilized mutant lipase (MAS1‐H108A)‐catalyzed esterification of glycerophosphorylcholine (GPC) and CLA‐rich FAs. Under the optimized conditions (temperature of 55 °C, substrate molar ratio of CLA‐rich FAs to GPC of 40:1, and enzyme loading of 300 U g−1), LPC content as high as 89.10 mol.% is achieved, which is exceptionally higher than any ever‐reported value. By monitoring the esterification process, it is found that sn1‐LPC is easy to synthesize and is the predominant product, while sn2‐LPC and phosphatidylcholine (PC) are difficult to synthesize and are with lower content in the final product. The formed sn2‐LPC during esterification may mainly attribute to the acyl migration of sn1‐LPC and the ratio of sn1‐LPC to sn2‐LPC finally plateaus at approximately 7. Besides, our results also demonstrate that sn2‐LPC is the main template for the synthesis of PC. Finally, a complete reaction scheme for the synthesis of LPC by immobilized MAS1‐H108A‐catalyzed esterification of GPC and fatty acids is mapped out. Overall, the highest LPC content can be obtained by immobilized MAS1‐H108A‐catalyzed esterification and there is the first study for systematical studying the reaction process of CLA‐rich LPC synthesis.